Field-based investigation of aged biochar coupled with summer legumes effect on wheat yield in Pakistan - Hafeez Ur Rahim; Sajjad Ahmad; Zaid Khan; Muhammad Ayoub Khan (Buletin Agroteknologi, 2020)
There is a debate about the effect of the aged biochar on the crop yield. Herein, a field-based experimental data set and analysis provide the information on the effect of the aged biochar coupled with summer legumes on the yield of wheat. During summer 2016, three different legumes (mungbean, sesbania, and cowpea) were grown with the intention of grain for human consumption, green manuring for soil fertility improvement and fodder for livestock consumption. A fallow (control) was also included in the experiment with the purpose of comparison. Biochar was applied to each experimental plot in triplicates at the rate of 0, 5, and 10 tons ha-1. Afterward, the harvesting of legumes, the biomass of the sesbania treatment plot, was mixed in the field, although the biomass of mungbean and cowpea were detached from each respective plot. The wheat crop was grown on the same field layout and design (randomized complete block) of legumes. The data analysis highlighted that significantly maximum grain yield (kg ha-1), biological yield (kg ha-1), thousand-grain weight (g), and straw yield (kg ha-1) were obtained in the plots mixed with sesbania. Regarding the aged biochar effect, maximum yield was obtained in the plots with 10 tons ha-1 treatment. Additionally, the interaction of aged biochar, coupled with legumes, was non-significant. In conclusion, this work could prove that aged biochar, coupled with summer legumes enhanced the yield of wheat on a sustainable basis due to its numerous benefits to the plant system.